The Effect of Using Wayground Media on Improving the Learning Motivation of Fifth-Grade Elementary School Students in Learning Fractions - Jihan Saraswati Ginting; Alman Alman; Heny Sri Astutik (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the effect of using the Wayground platform on the learning motivation of fifth-grade elementary school students in the subject of fractions. The main issue in this study is the low level of student motivation in mathematics learning, which is abstract and unengaging. This study employs a quantitative approach with a quasi-experimental design using a pretest-posttest model. The research sample consisted of 21 students selected using purposive sampling. The instrument used was a learning motivation questionnaire based on a Likert scale. The results of the study indicate a significant increase in students’ learning motivation following the use of the Wayground media. The average learning motivation score increased from 18.76 (moderate category) to 26.95 (good category). The results of the paired-sample t-test showed a t-value (20) = 19.61 with p < 0.001, indicating a significant difference between pre- and post-intervention. Additionally, the effect size of Cohen’s d = 4.28 indicates that the effect is very large. The conclusion of this study indicates that the Wayground platform is effective in enhancing students’ learning motivation regarding fractions. The implications of this study highlight the importance of integrating gamification-based digital learning platforms into the learning process to increase student engagement and motivation. This study contributes to the development of innovative technology-based learning strategies in elementary schools